Utilization of Lignocellulolytic Probiotic Bacteria Consortium as Microbial Protein - Mudita, I.M.; Partama, I.B.G.; Sutama, I.N.S.; Suberata, I.W.; Ariana, I.N.T. (Pakistan Journal of Nutrition, 2023)
Background and Objectives: While the use of AGPs is band, the development of a competitive and sustainable livestock business faces various challenges, mainly related to the low quality and quantity of local feed. This study aimed to create a synergistic formula of lignocellulolytic probiotic bacteria for the production of microbial protein functional feed that can be used as a substitute of antibiotics growth promoters for the development of competitive and sustainable livestock. Materials and Method: The microbial protein feed was formulated using a superior lignocellulolytic probiotic bacteria isolated from Bali cattle rumen fluid and termites, namely 1)Bacillus subtilis strain BR4LG, Bacillus subtilis strain BR2CL, Aneurinibacillus sp. strain BT4LS, Bacillus sp. strain BT3CL and 5)Bacillus sp. strain BT8XY. “Microbial Direct Feed” formulas were FB0, FB1, FB2, FB3, FB4 and FB5. The nutrient contents, bacteria population, metabolic producet, dry matter and organic matter of in vitro digestibility and amino acids profile were used to evaluate the quality of microbial protein feed. Analysis of variance (ANOVA) was used to analyze the data followed by HSD test for comparison among treatments. Results: In comparison with the control feed (FB0), lignocellulolytic probiotic bacteria produced higher quality (nutrients contents, bacteria population, metabolite substrates and in vitro digestibility) of microbial proteins feed (FB1234, FB1235, FB1245 and FB12345). Bacterial consortium formula FB12345 produced high quality microbial protein feed with the highest nutrients content, bacterial population, metabolite substrates, in vitro digestibility and amino acids profile. Conclusion: The probiotic lignocellulolytic bacteria consortium with formula FB12345 can produce microbial protein feeds of the highest quality.